Characteristics of Thermoresponsive Biohydrogels - Bożena Tyliszczak; Magdalena Bańkosz; Klaudyna Grzela; Korneliusz Rzepka; Monika Iglar; Jakub Piątkowski; Katarzyna Sala; Aniela Woźniak; Dominika Wanat; Magdalena Kędzierska (Engineering Proceedings, 2023)
The aim of this work was the synthesis of functional hydrogel materials obtained via photopolymerization. The resulting systems were characterized in terms of chemical structure using Fourier transform infrared spectroscopy. Subsequently, their sorption capacity and surface morphology were determined along with roughness analysis. The resulting materials have been modified with fluorescein dye and can be used in many branches of industry and medicine, for example, in innovative diagnostic systems.